An evaluation of conventional and no-tillage systems on soil physical conditions. - Nzeyimana, Innocent. (2011)
The use of no-tillage (NT) system has increased in the past few years in South Africa, but its effects on soil physical conditions have not been adequately documented. This study was undertaken to ascertain these effects, as compared to Conventional tillage (CT) system. Several sites were selected in the Bergville and Winterton areas of the midlands of KwaZulu-Natal, and at the Cedara Agricultural Research Station. NT generally increased bulk density in the topsoil and this altered total porosity and poresize distribution. Water retention, organic C and aggregate stability were increased under NT, partly due to the maintenance of the mulch cover on the surface soil. Organic C and aggregate stability were positively correlated with each other. Differences in bulk density between tillage systems with soil depth did not clearly indicate where soil compaction had occurred. Significant differences in soil compaction between treatments were, however, illustrated by changes in soil penetration resistance (SPR), especially at the. 150 mm depth. In addition, depending on the soil type, SPR was greater in the topsoil under NT than CT. It was suggested that conversion from CT to NT was carried out when the topsoil of the CT-fields was structurally poor, due to a previous history of continuous CT. Tractor traffic under CT and repeated tillage when the soil was wet had, in some cases, resulted in the formation of a compacted layer at the depth of cultivation. In clay soils, this has resulted in subsoil compaction. The formation of compacted layers caused major changes to pore size distribution and continuity and this resulted in substantially reduced hydraulic conductivity, infiltration rate,air-filled porosity and air permeability. It was concluded that compacted subsoil layers need to be broken up prior to conversion from CT to NT, and that compaction in the surface soil under NT has occurred and, in some cases, this will be a limitation to crop production. The use of minimum tillage systems should be considered and researched in these cases. === Thesis (M.Sc.)-University of Natal, Pietermaritzurg, 2003.